2015
DOI: 10.1038/srep17665
|View full text |Cite|
|
Sign up to set email alerts
|

Heterologous expression of newly identified galectin-8 from sea urchin embryos produces recombinant protein with lactose binding specificity and anti-adhesive activity

Abstract: Galectin family members specifically bind beta-galactoside derivatives and are involved in different cellular events, including cell communication, signalling, apoptosis, and immune responses. Here, we report a tandem-repeat type galectin from the Paracentrotus lividus sea urchin embryo, referred to as Pl-GAL-8. The 933nt sequence encodes a protein of 34.73 kDa, containing the conserved HFNPRF and WGxExR motifs in the two highly similar carbohydrate-recognition domains (CRD). The three-dimensional protein stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Notably, the levels of these proteins in the sea urchin secretome exposed to TiO 2 NPs for 24 h was lower than that for the controls, perhaps because these proteins were sequestered on the particle surface. Both sea urchin toposome and nectin are glycoproteins (28, 35), while galectin-8 binds glycoproteins (36). Glycoproteins have good binding affinity to TiO 2 NP particle surface (37).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the levels of these proteins in the sea urchin secretome exposed to TiO 2 NPs for 24 h was lower than that for the controls, perhaps because these proteins were sequestered on the particle surface. Both sea urchin toposome and nectin are glycoproteins (28, 35), while galectin-8 binds glycoproteins (36). Glycoproteins have good binding affinity to TiO 2 NP particle surface (37).…”
Section: Resultsmentioning
confidence: 99%
“…cDNA diluted 1:5 with H 2 O was used in Real Time qPCR experiments as described previously 24 . The data were normalized for the reference gene PlZ12-1 , which resulted to be the most suitable reference gene in previous studies 24 25 56 57 58 59 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Pl -CAN was among the 10 occluded proteins identified, which were tightly bound to the mineral phase, and was present in both acetic acid-soluble and -insoluble matrices of the skeletal test tissues. By an in vitro crystallization assay, authors showed that this set of proteins has a shaping effect on the biocalcite formation, thus providing new information to the biologically controlled mineralization hypothesis [ 40 ]. The presence of Pl -CAN in adult tests was confirmed by WB using the same homologous polyclonal antibody used here to verify the presence of Pl -CAN in AZ-treated embryos ( figure 1 b this manuscript), indicating that Pl -CAN is a component of both embryonic and adult skeletal matrix and thus suggesting that it might have a similar behaviour in the adult and embryonic biomineralization processes.…”
Section: Discussionmentioning
confidence: 99%